An Assessment of Medical Physics Knowledge of Undergraduate Physics Students - Ali, S.; Hussain, A. (The Nucleus, 2016)
Medical physics in an applied branch of physics in which physics principle applied in medicine. With the tremendous advancement in diagnostic and therapeutic site medical physics had taken more intention. In this study we assessed the medical physics knowledge of the undergraduate physics students. The study includes 2nd year (n=180), 3rd year (n=140) and final year students (n=70), studying physics as a major subject. The paper comprises of 12 MCQ’s that covers radiology, radiation physics, radiation protection and physics of radiation therapy. The students were given 12 minutes to answer the questions. On average 56 (31.2%) students from second year answer the paper correctly. This value increased to 57(41%) and 35(50%) for the third and final year students. Only 33(17%) students of the second year gave the correct answer to the radiation oncology section. The results slightly increased to 23% (n=33) for the third year students. The final year students performed better and the passing score was 28.1% (n=19) in this section. All the students performed better in radiation physics section, where the overall scores for 2nd, 3rd and 4th year were 47.2%(n=85), 54.8%(n=77) and 55.7%(n=39) respectively. From this study we conclude that the final year students have significant knowledge in all four areas.